Aristotle: A Very Short Introduction - Barnes, Jonathan (New York Oxford University Press, 2000)
In this book, Jonathan Barnes examines Aristotle's scientific researches, his discoveries in logic and his metaphysical theories, his work in psychology and in ethics and politics, placing his teachings in their historical context.
Includes Index and Illustrations
Keywords: Aristotle -- Criticism and interpretation